Quality of life following LASIK surgery at a tertiary center in North India: Quality of life following LASIK surgery - Kumar, Anil; Jha, Ujjwal Prakash; Kumar, Suresh; Arya, Sudesh Kumar; Rani, Deepika; Kumar, Vinod; Pathmanathan, Gayathiri (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Laser-assisted in situ keratomileuses (LASIK) refractive surgery is a cutting-edge and developing area of ophthalmology. Reshaping the cornea during refractive surgery helps patients become less dependent on glasses or contact lenses. The aim of the present study was to evaluate the visual outcome, quality of life, and patient satisfaction following LASIK surgery at a tertiary care center in North India using the National Eye Institute Refractive Error Quality of Life (NEIRQL-42) questionnaire. Methods: NEI-RQL, a 42-item measure with 13 subscales. The questionnaire was administered to a sample size of 71 patients who underwent LASIK Surgery at a tertiary center in North India. Data were collected pre- and post-surgery (1,3,6 month post-LASIK) for myopic or hyperopic refractive error. Statistical analysis was done using the Friedman test and Wilcoxon signed-rank test. Results: In myopic patients, the mean preoperative spherical equivalent (SE) was -4.19 ± 2.28D in the right eye and -4.26 ± 2.28D in the left eye and post-op SE -0.06±0.29 (p=0.00). The largest improvements (>25 points) on the 0 to 100 possible score range, were seen in activity limitations, dependence on correction, appearance, and satisfaction with correction subscales. The subscale glare showed a statistically significant difference (worsening) whereas a non-significant change (P> 0.05) was recorded only in the sub-optimal correction sub-scale. Conclusions: The NEIRQL-42 is a responsive tool to evaluate vision-related changes in quality of life after LASIK surgery in the Indian population. The best surgical expectancy and QoL can be expected at 6 months following surgery.